Aerodynamic effects on outer ash deposition rates in second generation atmospheric pressure oxy-coal combustion systems. (1st November 2021) - Krishnamoorthy, Gautham; Kuznia, Monika E.; Smith, KayLee M.; Seames, Wayne S.; Wang, Yueming; Wendt, Jost O.L.
Highlights: Ash deposition modeled in scenarios encompassing significant flow rate variations. Impaction rates and deposition characteristics assessed through deposition module. Accurate parent fuel PSD deemed insufficient to predict accurate deposition trends. Changes to parent fuel PSD to match the measured deposit PSD improved agreement. Comparing deposition rates between AIR/OXY combustion depends on accurate ash PSD. Abstract: Recent measurements in scenarios representative of second generation atmospheric pressure oxy-coal combustion systems have shown a significant increase in ash deposition rates in comparison to combustion in air. However, the causative mechanisms behind this increase have not been well understood. To fill this void, well-characterized experiments including fuel and deposit particle size distributions (PSDs) were coupled with highly resolved numerical simulations to isolate the aerodynamic effects impacting the deposition process such that mechanisms could be hypothesized. Three combustion scenarios (AIR, OXY27, OXY70) spanning a factor of three variation in flue gas volumetric flow rates were simulated and the deposition characteristics (impaction rates, deposit PSD, temperature, residence times, capture rates) tracked/predicted using a customized deposition module. The measured deposit PSD was significantly different from the PSD of the parent fuel indicating significant physio-chemical transformations (coalescence and particle growth in particular) at play. The use of simplistic modeling approaches (swelling parameter variations) to model particle growth led to inaccurate deposit ash PSD and rate predictions. A more satisfactory agreement between the measurements and simulations was obtained when the functional form of the parent fuel PSD (spread parameter) was modified to conform closely to the deposit PSD while still ensuring the fidelity of temperature and velocity predictions. Based on the measured ash compositions, identical capture criteria were employed across all three scenarios. This study further supports the theory that the ash deposition rates in these systems are dominated by aerodynamic effects with the ash PSD playing a dominant role.